MODEL PENDIDIKAN KECAKAPAN HIDUP BAGI REMAJA MISKIN PUTUS SEKOLAH DALAM USAHA HIDUP MANDIRI MELALUI PELATIHAN KEWIRAUSAHAAN - Wasisto, Edhi (-)
The research aims to improve the skills of the model life skills education for school drop outs to be able to live independently through entrepreneurship training. The study consisted of three variables: (1) the intensity of service models; (2) poor work skills teens drop out of school; (3) the effectiveness of service models. The research method is a survey, observation, interviews, questionnaires, and documentation. Research held in the village Jurug and Jaten Palur subdistrict, Karanganyar, conducted in April-October 2014. In this study the approach of action research (action research), experiments, interviews, observation, demonstration / training, assignments to the subject of research and evaluation. Quantitative data analysis using descriptive quantitative approach, qualitative data using an interactive approach. Results: (1) obtained from the data base of potential villages in the area of research relating to problems of poor teenage dropouts in rural areas; (2) obtained baseline prevalence of poor teenage dropout from the education level and distribution that need life skills education services; (3) known to need assessment of impoverished youths drop out of school; (4) can be arranged modules educational material related to life skills needs of impoverished youths drop out of school; (5) can be prepared team implementing the model; (6) can be trained a number of 10 teams driving and implementing the model; (7) can be educated some 30 impoverished youths drop out of school, (8) can be written journals of national accredited; (9) can be written handbook lecture on life skills education and entrepreneurship.Keywords: Model of entrepreneurship educationÂ  for poor teens drop out of school through entrepreneurship training;